2018
DOI: 10.1038/s41419-018-1028-5
|View full text |Cite
|
Sign up to set email alerts
|

The proline–arginine repeat protein linked to C9-ALS/FTD causes neuronal toxicity by inhibiting the DEAD-box RNA helicase-mediated ribosome biogenesis

Abstract: A GGGGCC repeat expansion in the C9ORF72 gene has been identified as the most common genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia. The repeat expansion undergoes unconventional translation to produce dipeptide repeat (DPR) proteins. Although it has been reported that DPR proteins cause neurotoxicity, the underlying mechanism has not been fully elucidated. In this study, we have first confirmed that proline–arginine repeat protein (poly-PR) reduces levels of ribosomal RNA and cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 51 publications
4
38
0
Order By: Relevance
“…This suggests a ribosomal dysfunction, which implies a defect in RNA translation. In line with these findings, a recent report demonstrated that poly-PR co-localizes with the nucleolar protein, nucleophosmin, and reduces the expression of several ribosomal RNA (Suzuki et al, 2018). Suzuki et al (2018) further showed that the reduction in the expression of ribosomal RNA results in neuronal cell death and this could be rescued by overexpression of an accelerator of ribosome biogenesis, Myc (Suzuki et al, 2018).…”
Section: C9orf72 Intronic Expansionsupporting
confidence: 57%
See 1 more Smart Citation
“…This suggests a ribosomal dysfunction, which implies a defect in RNA translation. In line with these findings, a recent report demonstrated that poly-PR co-localizes with the nucleolar protein, nucleophosmin, and reduces the expression of several ribosomal RNA (Suzuki et al, 2018). Suzuki et al (2018) further showed that the reduction in the expression of ribosomal RNA results in neuronal cell death and this could be rescued by overexpression of an accelerator of ribosome biogenesis, Myc (Suzuki et al, 2018).…”
Section: C9orf72 Intronic Expansionsupporting
confidence: 57%
“…In line with these findings, a recent report demonstrated that poly-PR co-localizes with the nucleolar protein, nucleophosmin, and reduces the expression of several ribosomal RNA (Suzuki et al, 2018). Suzuki et al (2018) further showed that the reduction in the expression of ribosomal RNA results in neuronal cell death and this could be rescued by overexpression of an accelerator of ribosome biogenesis, Myc (Suzuki et al, 2018). RNA sequencing reveals that more than 6,000 genes are up or down regulated in mice that express the dipeptide construct in the brain (Zhang et al, 2018c).…”
Section: C9orf72 Intronic Expansionsupporting
confidence: 57%
“…These constructs displayed patterns of localization and toxicity in the mouse neuroblastoma cell line Neuro2a similar to that described previously in other models (26)(27)(28)(29)(30)(31) and observed in vivo for cases of MND with C9ORF72 mutation (5,8,13,32,33). This included a predominately nuclear punctate pattern of localization for PR10 and PR101 with residual expression in the cytosol (Fig 1A).…”
Section: Resultssupporting
confidence: 78%
“…Providing new insight into the mechanism by which poly(GA) deposition promotes UPS impairment (Guo et al, 2018), a recent study utilized cryo-electron tomography to demonstrate that 26S proteasome complexes are sequestered within poly(GA) aggregates. Although less abundant than poly(GA), the arginine-rich poly(PR) and poly(GR) proteins appear to be particularly toxic in cultured cell, fly, and yeast models, with nucleolar stress, reduced ribosomal biogenesis, translational impairment, altered SG dynamics, and nucleocytoplasmic transport abnormalities implicated in the mechanism of toxicity (Freibaum et al, 2015;Hartmann et al, 2018;Jovi ci c et al, 2015;Kanekura et al, 2016;Kwon et al, 2014;Mizielinska et al, 2014;Suzuki et al, 2018;Tao et al, 2015;Wen et al, 2014;Zhang et al, 2018b). While a poly(PR) mouse model has not yet been developed, poly(GR) expression in vivo is associated with more severe neurodegeneration than poly(GA), with toxicity driven by reduced protein translation resulting from poly(GR)mediated sequestration of ribosomal subunits and the translation initiation factor eIF3h (Zhang et al, 2018b).…”
Section: Pathogenic Mechanisms Implicated In Alsmentioning
confidence: 99%